1996
DOI: 10.1007/s004360050114
|View full text |Cite
|
Sign up to set email alerts
|

New trends in chemotherapy on human and animal blood parasites

Abstract: Blood-parasite protozoa are causative agents of some of the major tropical or infectious diseases for humans and animals, such as Plasmodium for malaria (about 270 million infected people), Trypanosoma cruzi for Chagas' disease (about 18-20 million individuals), African trypanosomes for human and bovine trypanosomiasis, and Babesia for cattle and dogs. The absence of efficient vaccines against these diseases, the absence or the high toxicity of the few drugs against American and African trypanosomiasis, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Trypanosome infections are known to cause immunosuppression responsible for the host's inability to eliminate the trypanosomes even after administration of trypanocidal drugs (Godwin et al, 1972;Osma et al, 1992) Diminazene aceturate and isomethamidium chloride are the most currently used trypanocides, used both for prophylactics and curative purposes for the control of the disease in cattle (WHO, 1995). Unfortunately the parasite have developed resistance to these drugs (Schrevel et al, 1996;Anene et al, 2000;Geerts et al, 2001) which makes the search for efficacious chemotherapeutic agents from locally available ethnomedicinal plants for use as trypanocidal agents necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Trypanosome infections are known to cause immunosuppression responsible for the host's inability to eliminate the trypanosomes even after administration of trypanocidal drugs (Godwin et al, 1972;Osma et al, 1992) Diminazene aceturate and isomethamidium chloride are the most currently used trypanocides, used both for prophylactics and curative purposes for the control of the disease in cattle (WHO, 1995). Unfortunately the parasite have developed resistance to these drugs (Schrevel et al, 1996;Anene et al, 2000;Geerts et al, 2001) which makes the search for efficacious chemotherapeutic agents from locally available ethnomedicinal plants for use as trypanocidal agents necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The need for additional trials to study whether enrofloxacin is useful to control severe anaplasmosis infections has been identified . Schrevel et al (1996) recently reviewed new trends in chemotherapy of human and animal blood parasites. These workers highlight a recent study that demonstrated activity of the 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors, Lovastatin and Simvastatin against in vitro cultured Plasmodium falciparum and B. divergens (Grellier et al, 1994).…”
Section: Future Developments In the Field Of Chemosterilization Of Pementioning
confidence: 99%
“…In addition to these agents, Schrevel et al (1996) describe studies examining the effect of microtubular drugs, paclitaxel (Taxol) and its analog, docetaxel (Taxotere), on P.…”
Section: Future Developments In the Field Of Chemosterilization Of Pementioning
confidence: 99%